Analytical approach to electrical distribution systems for aircraft - Spagnolo, Cosimo (2022)
The More Electric Aircraft concept (MEA) is one of the most discussed topics of the recent decades inside the aircraft market. It aims to enable the migration towards more efficient aircraft while reducing the environmental impact by substituting the hydraulic, pneumatic and mechanical parts with their electrical counterparts. As the electrical systems became more complex, it is inevitable the need of a control unit that can manage the EPS under all the possible scenarios. For this reason, this thesis presents different study cases that a supervisor controller (SC) unit must address for guarantying the optimal EPS operations. In particular, the SC must be able to manage the network overloads, for preventing unwanted operations or oversized design of the on-board generators. Moreover, applying constant EPS monitoring, the SC must be able to solve critical scenarios by splitting the power flow on a different path. Apart from failure and critical tasks, the SC must be also employed in the EPS optimization using a mathematical algorithm that ensures the correct power spreading across each bus. After the introduction to the actual employed algorithms and used EPS, all the described cases are simulated inside Simulink® environment and a test bench is then configured to emulate a portion of a scaled EPS in the laboratory.